A Review on Functional Analyses of Tics. Issue 2 (March 2020) - Goldman, Kissel J.; DeLeon, Iser G.
Tic disorders are characterized by a class of responses assumed to be neurobiological in origin. Still, several studies have shown that tic frequency can be influenced by antecedent environmental events and social consequences. Prior reviews have summarized the effects of environmental events but have not examined relations between tic diagnosis, behavioral deficits (e.g., intellectual disability), tic topography, and the consequences observed to maintain tics. These variables might be important when attempting to predict or identify relevant consequences. A more thorough understanding of the variables that maintain and give rise to tics might also be useful in predicting responsiveness to treatment and intervention refinement. We reviewed and summarized results from the 13 attempts to experimentally identify maintaining consequences for tics (i.e., functional analyses) that have been published to date. We examined patterns of functions across tic diagnoses (i.e., Tourette's syndrome or not), communication impairments (i.e., an intellectual disability or reported language difficulty), and tic topography. Results suggested that individuals with Tourette's syndrome and those without communication impairments are more likely to have functional analysis outcomes consistent with automatic reinforcement, but exceptions in both directions highlight the utility of functional analysis in treating tics.